PEMECAHAN MASALAH MATEMATIKA ANAK PEMULUNG DI PERKAMPUNGAN WADUK PERMAI - Lestari, Siska (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2017)
AbstractThis research aims to describe problem solving in mathematics by the scavengers of Waduk Permai Village. The methodology of research that usedÂ  is descriptive methodology in a form of study case. Subjects in this research are 3 scavenger children. Instruments of data collection which used for support researcher are interview and written test. The interview are used for describe how the process of problem solving to the scavengers, at the same time the test are used for giving the way and support of the interview result. The results of the analysis concluded that problem solving of scavengers to finish varied question of the test are inconsistent using step by step on each given question. Beside that, scavenger children not yet fully follow the steps on finishing questions of the test that as Polya said.Keywords: Problem Solving, The Scavengers